The Scruffy Sea Otter - Cobb, Amelia; Williams, Sophy (London : Nosy Crow, 2017)
Zoe is SO excited when Great Uncle Horace brings THREE gorgeous sea otter pups to live at the Rescue Zoo! The orphaned pups are very fluffy and cheeky - and the youngest pup, Sasha, is the cheekiest and fluffiest of all. Zoe uses her special skills to talk to the otters and gets to know them all very well. But Sasha feels sad when her older, more confident, siblings are chosen to take part in a special otter display. Can Zoe and Meep persuade Sasha the scruffy sea otter not to give up and to bring her own special skills to the show?
4.8
3-6.
3-6
Keywords: Seals (Animals) -- Juvenile fiction; Zoos -- Juvenile fiction; Seals (Animals) -- Fiction; Zoos -- Fiction; Seals (Animals) -- Fiction; Zoos -- Fiction